Navigating Artificial Intelligence in the Successful Implementation of Inclusive Education Practices - Vivekanantharasa, Raveenthiran (Sekolah Tinggi Manajemen IPMI, 2025)
In the present world, Artificial Intelligence (AI) is referred to as intelligent systems based on enormously large datasets that are capable of analyzing their surroundings in order to fulfil specific tasks in different fields. Like the influence of artificial intelligence impacts on different careers to achieve great feats, inclusive education is one important area that influences and develops by the integration of artificial intelligence in the successful implementation of inclusive education practices. This article mainly discusses how Artificial Intelligence (AI) is leveraged within educational environments to support students with disabilities and inclusive strategies and experiences. The main question connected with this article concerns about that the role and impact of AI across diverse educational settings and, in particular: “How is Artificial Intelligence (AI) being utilized within educational settings to support individuals with disabilities and promote inclusive education?” Focusing various educational strategies in teaching and learning for students in inclusive education practice this article aims to describe the key ideas of the article. In 21st century education system, inclusive education plays a pivotal role in reaching the quality level of education by helping students with special needs. Therefore, this article highlights the role of Artificial Intelligence in the successful implementation of inclusive education.